A study on the relationship between co-curricular and grades among fourth year students of San Jose National High School S.Y. 1998-1999 - De La Sierra, Elvira A. (1999)
The study was conducted to determine the relationship between Co- Curricular Activity and Grades among Fourth Year students of San Jose National High School. This was also done to determine the underlying reasons and effects to students who are involved or not involved to at least one or more than one Co- Curricular Activity based on their Second Grading Period. There are 63 respondents who were taken randomly from six sections by using 19% of the total population to determine the sample size. The researcher deliberately made the questionnaire. There are two variables investigated in this study: Co- Curricular Activity and Grades of the respondents.
After gathering the data, the researcher tabulated, tallied and analyzed the collected data according to frequency, averages, percentages, and t-test value. The researcher found out that various reasons and effects existed depending on the individual respondents. Co- curricular activity is widely participated by diligent and excellent students in the campus. The mean of one or no Co-Curricular group is not significantly different from the mean of more than one Co- Curricular group at 0.05 level of significance. If there is any relationship, it is visible only during a very tight competition of honor students because it receives additional points. Therefore, there is no relationship between Co-Curricular activity and Grades among Fourth Year students of San Jose National High School.
Undergraduate thesis (B.A.S.S. Psychology) -- University of the Philippines, Tacloban.
Keywords: Relationship of Cu- Curricular Activity and Grades; Social Science